A STUDY OF THE PSYCHOLOGICAL ASPECTS OF THEMAIN CHARACTERS IN WEI HUI’S NOVEL SHANGHAI BABY - Dwi Aprilina Setiarini (Indonesian Publication Center, 2020)
This study investigates the psychological aspects of the main characters in Wei Hui?s novel Shanghai Baby. Researcher describes and identifies the characteristics of main characters personality related to Sigmund Freud?s theory (Id, Ego, Superego). In this study researcher uses qualitative approach withdescriptive method or commonly referred to as qualitative descriptive method. Data are collected from variety of sources such as the novel, books, journal, online website, and some additional information. The findings from the study, the writer found there are six personalities of the main characters in Sanghai Baby Novel, such as ambitious, lustful, restless, sensitive, introvert and extrovert, the writer also found the relationship between the characteristics with the theory of Sigmund Freud (Id, Ego, Superego).